Socioeconomic disparities in childhood vaccine hesitancy among parents in China: The mediating role of social support and health literacy - Xuelin Yao; Mao Fu; Jin Peng; Da Feng; Yue Ma; Yifan Wu; Liuxin Feng; Yu Fang; Minghuan Jiang (Human Vaccines & Immunotherapeutics)
Parental vaccine hesitancy is a major obstacle to childhood vaccination. We examined parental socioeconomic status (SES) disparities in vaccine hesitancy, and the potential mediating roles of perceived social support and health literacy. A questionnaire survey was given to parents with children aged below 6 years from six provinces in China. SES was examined by educational attainment, annual household income, and a subjective measure of SES (using a scale of 1–10). Linear regression was applied to assess the association between SES and vaccine hesitancy. Bootstrapping mediation analysis was performed with 5,000 samples bootstrapped. A total of 1,638 parents were included. Using annual household income > 200,000 Chinese yuan (CNY) as a reference, parents with lower household income (CNY 100,001–150,000) experienced higher vaccine hesitancy. Educational attainment was not associated with vaccine hesitancy. Subjective SES had a U-shaped relationship with vaccine hesitancy. Perceived social support and health literacy independently and sequentially mediated the effects of subjective SES (indirect effect: −0.240) and annual household income (indirect effect: 1.250 for ≤ CNY 100,000 and 0.759 for CNY 100,001–150,000) on vaccine hesitancy. Socioeconomic disparities influenced parental vaccine hesitancy in China, which were mediated by perceptions of social support and health literacy.